Evaluation of Acellular Dermal Matrix Efficacy in Prosthesis-Based Breast Reconstruction. Issue 3 (March 2018) - Sobti, Nikhil; Ji, Emily; Brown, Rebecca L.; Cetrulo, Curtis L.; Colwell, Amy S.; Winograd, Jonathan M.; Austen, William G.; Liao, Eric C.
Abstract : Background: Although many studies have examined the safety of acellular dermal matrix in immediate prosthetic breast reconstruction, few studies have evaluated efficacy. This study examined initial tissue expander fill volume as a marker of efficacy, comparing patients after staged prosthetic breast reconstruction assisted with acellular dermal matrix versus breast reconstruction not assisted with acellular dermal matrix. Number of fill visits and time interval to implant exchange were examined as secondary endpoints. Methods: An institutional review board–approved retrospective chart review was conducted to identify consecutive staged prosthetic reconstruction cases over 12 years. Results: Mean initial tissue expander fill volume was significantly higher in the acellular dermal matrix group compared with the non–acellular dermal matrix group (180.8 ± 150.0 versus 45.8 ± 74.4; p = 0.00). Normalizing for final implant size, the acellular dermal matrix group exhibited significantly higher perioperative fill (0.33 ± 0.24 versus 0.11 ± 0.16; p = 0.00). A collinear trend was observed between acellular dermal matrix use and direct-to-implant reconstruction procedures during the study period. Conclusions: These results suggest that acellular dermal matrix use is more efficacious in achieving greater initial fill volume, fewer visits for expansion, and a shorter time interval to implant exchange compared with non–acellular dermal matrix procedures. The authors also describe a collinear relationship between acellular dermal matrix use and transition to direct-to-implant procedures at their institution. This work serves as a framework for future studies evaluating acellular dermal matrix efficacy, and guides innovation of biomaterials to support breast reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : This and Related "Classic" Articles Appear on Prsjournal.com for Journal Club Discussions.